Sex differences in cognition among Chinese people with Parkinson's disease. Issue 3 (March 2015) - Gao, Liang; Nie, Kun; Tang, Hongmei; Wang, Limin; Zhao, Jiehao; Gan, Rong; Huang, Jing; Feng, Shujun; Zhu, Ruiming; Duan, Zhenpeng; Zhang, Yuhu; Wang, Lijuan
Abstract To investigate sex differences in cognitive function in Parkinson's disease patients, a cohort of 172 male patients and 139 female patients were recruited for this study. Their demographic and clinical features, including age, disease duration, education level, Unified Parkinson's Disease Rating Scale-III, Hoehn–Yahr Scale, activities of daily living, Hamilton Depression Rating Scale and Hamilton Anxiety Rating Scale score were recorded. The Mini Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Wechsler Adult Intelligence Scale-Chinese Revision (WAIS-RC) and Wechsler Memory Scale-Chinese Revision (WMS-RC) scores were compared to distinguish the cognitive properties between the two groups. The MMSE values did not show a significant difference between the groups. However, the MoCA scores of male patients were significantly higher than those of female patients (adjusted p < 0.05). The male group demonstrated better performances with respect to visuospatial function, naming and abstraction (adjusted p < 0.05). The WAIS-RC data showed that female patients had lower scores in information, vocabulary, picture completion, block design and picture arrangement (adjusted p < 0.05), and the WMS-RC data showed that 100-1 and cumulative addition abilities were significantly weaker in females than males (adjusted p < 0.05). Cognitive disturbances were more prevalent and severe in women among Chinese Parkinson's disease patients.